An overview of non-contact photoplethysmography [Temassiz Fotopletismografiye Genel Bakiş] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2017)
Photoplethysmography (PPG) is a method which is used to extract physiological parameters such as heart pulse rate, respirotary rate, and their variation with respect to time by optically measuring the blood volume change in the tissue. Photoplethysmography methods can be categorized into two groups: contact and non-contact. An example of contact photoplethysmography is the fingertip pulse oximetre which is widely used in medical centers. In non-contact photoplethysmography, with the use of special or commonly used cameras, these parameters are extracted from the color changes especially around the face caused by heart beat. In this survey, we aimed to provide information about the important studies in the literature, as well as to introduce the areas for improvement. © 2017 IEEE.
Keywords: heart pulse rate; non-contact photoplethysmography; photoplethysmography; respirotary rate